2015
DOI: 10.1111/bjhp.12152
|View full text |Cite
|
Sign up to set email alerts
|

Is the intention–behaviour gap greater amongst the more deprived? A meta‐analysis of five studies on physical activity, diet, and medication adherence in smoking cessation

Abstract: ObjectivesUnhealthy behaviour is more common amongst the deprived, thereby contributing to health inequalities. The evidence that the gap between intention and behaviour is greater amongst the more deprived is limited and inconsistent. We tested this hypothesis using objective and self‐report measures of three behaviours, both individual‐ and area‐level indices of socio‐economic status, and pooling data from five studies.DesignSecondary data analysis.MethodsMultiple linear regressions and meta‐analyses of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 74 publications
5
30
0
Order By: Relevance
“…() reporting closer relationships between intention and behaviour in people living in more affluent areas, whereas Vasiljevic et al . () found no such moderation effects. However, it can be argued that neither study has adopted a real multilevel perspective, as both have matched environment‐level data to individual data – with the potential of committing an ecological fallacy (Robinson, ).…”
Section: Environment‐level Facets Of Ses – Need For a Multilevel Resementioning
confidence: 84%
See 1 more Smart Citation
“…() reporting closer relationships between intention and behaviour in people living in more affluent areas, whereas Vasiljevic et al . () found no such moderation effects. However, it can be argued that neither study has adopted a real multilevel perspective, as both have matched environment‐level data to individual data – with the potential of committing an ecological fallacy (Robinson, ).…”
Section: Environment‐level Facets Of Ses – Need For a Multilevel Resementioning
confidence: 84%
“…() found education to moderate the effects of intention on physical activity and showed that this effect is in turn mediated by intention stability, suggesting that individuals with better education are better at forming stable and more robust intentions. On the other hand, a large study examining and meta‐analysing multiple health behaviours (Vasiljevic, Ng, Griffin, Sutton, & Marteau, ) found no moderating effects of education on the intention–behaviour relation or the relation between self‐efficacy and behaviour.…”
Section: Individual‐level Facets Of Ses and Theoretical Determinants mentioning
confidence: 97%
“…For example, Vasiljevic et al. () only found a significant moderation of the association between health cognitions and behaviour when area‐level SES measures were used but not individual‐level measures. This suggests that SES may have different effects depending on how it is defined and measured (Schüz, ).…”
Section: Discussionmentioning
confidence: 99%
“…() demonstrate a moderating effect of SES on the relationship between health cognitions and various health behaviours. Conversely, Vasiljevic, Ng, Griffin, Sutton, and Marteau () found no moderating effects of SES indicators on the relationship between intentions and behaviour. This study is notable, however, in that, contrary to a large body of literature, no significant main effects of intentions on behaviour are found.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, health psychology still needs a 'stronger consideration of SES' (Schuz, 2017,p.5). SES has already been shown to be associated with health behavioursfor example, physical activity (Vasiljevic, Ng, Griffin, Sutton, & Marteau, 2016) or early help-seeking for breast cancer (Marcu, Black, Vedsted, Lyratzopoulos, & Whitaker, 2016)but its role in the dehumanization of low-SES pain patients by health professionals is still poorly understood (Diniz, Bernardes, & Castro, 2019;Haslam & Stratemeyer, 2016).…”
mentioning
confidence: 99%